Grade groups at diagnosis in African Caribbean men with prostate cancer: Results of a comparative study. Issue 14 (2nd August 2019) - Meunier, Matthias E.; Tantot, Juliet; Neuzillet, Yann; Ghoneim, Tarek P.; Martin, François; Taouil, Touafik; Vignac, Maxime; Baumert, Hervé; Vinh‐Hung, Vincent; Dussaule‐Duchatelle, Véronique; Lebret, Thierry; Sutter, Willy; et al.
Abstract: Background: There are no comparative data on pathological predictors at diagnosis, between African Caribbean and Caucasian men with prostate cancer (PCa), in equal‐access centers. The objective of this study was to evaluate the grade groups of an African Caribbean cohort, newly diagnosed with PCa on prostate biopsy, compared with a Caucasian French Metropolitan cohort. Methods: A retrospective, a comparative study was conducted between 2008 and 2016 between the University Hospital of Martinique in the French Caribbean West Indies, and the Saint Joseph Hospital in Paris. Clinical, biological, and pathological data were collected at diagnosis. The primary outcome was the grade groups for Gleason score; the secondary outcome was the PCa detection rate. Multivariate analysis was performed using linear regression. Results: Of the 1880 consecutive prostate biopsy performed in the African Caribbean cohort, 945 had a diagnosis of PCa (50.3%) and 500 of 945 in the French cohort (33.8%). African Caribbean patients were older (mean 68.5 vs 67.5 years; P = .028), had worse clinical stage (13.2% vs 5.2% cT3‐4; P < .001) and higher median prostate‐specific antigen (PSA) level (9.23 vs 8.32 ng/mL; P = .019). On univariate analysis, African Caribbean patients had worse pathological grade groups than French patients ( P < .001). Nevertheless, after adjustment on age, stage, and PSA, there were no significant differences between the two cohorts ( P = .903). Conclusion: African Caribbean patients presented higher PCa detection rate, and higher grade groups at diagnosis than French patients in equal‐access centers on univariate analysis but not on multivariate analysis. African Caribbean patients with equivalent clinical and biological characteristics than Caucasian patients at diagnosis might expect the same prognosis for PCa.